Hepatic transferrin plays a role in systemic iron homeostasis and liver ferroptosis - Yu, Yingying; Jiang, Li; Wang, Hao; Shen, Zhe; Cheng, Qi; Zhang, Pan; Wang, Jiaming; Wu, Qian; Fang, Xuexian; Duan, Lingyan; Wang, Shufen; Wang, Kai; et al. (Blood, 2020)
Although the serum-abundant metal-binding protein transferrin (encoded by the Trf gene) is synthesized primarily in the liver, its function in the liver is largely unknown. Here, we generated hepatocyte-specific Trf knockout mice (Trf-LKO), which are viable and fertile but have impaired erythropoiesis and altered iron metabolism. Moreover, feeding Trf-LKO mice a high-iron diet increased their susceptibility to developing ferroptosis-induced liver fibrosis. Importantly, we found that treating Trf-LKO mice with the ferroptosis inhibitor ferrostatin-1 potently rescued liver fibrosis induced by either high dietary iron or carbon tetrachloride (CCl4) injections. In addition, deleting hepatic Slc39a14 expression in Trf-LKO mice significantly reduced hepatic iron accumulation, thereby reducing ferroptosis-mediated liver fibrosis induced by either a high-iron diet or CCl4 injections. Finally, we found that patients with liver cirrhosis have significantly lower levels of serum transferrin and hepatic transferrin, as well as higher levels of hepatic iron and lipid peroxidation, compared with healthy control subjects. Taken together, these data indicate that hepatic transferrin plays a protective role in maintaining liver function, providing a possible therapeutic target for preventing ferroptosis-induced liver fibrosis. •Trf-LKO mice display iron-deficiency anemia, iron overload in tissues, and susceptibility to liver damage via ferroptosis.•Ferroptosis inhibition or deletion of Slc39a14 attenuated iron overload and CCl4-induced liver fibrosis in Trf-LKO. [Display omitted]